Determinants of Financial Management Behavior Among SMES: The Role of Financial Knowledge, Attitudes, And Financial Planning in West Denpasar, Bali - Krisna, Ni Made Ayu; Widnyana, I Wayan; Tahu, Gregorius Paulus (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
MSMEs play an important role in the Indonesian economy, including in West Denpasar, Denpasar City, which continues to experience an increase in the number of business units. However, this development has not been fully accompanied by the ability of MSME players to manage their finances properly. This study aims to determine the effect of financial knowledge, financial attitude, and financial planning on the financial management behavior of SME actors in West Denpasar, Denpasar City. This study uses a quantitative approach with a sample size of 100 respondents selected using probability random sampling. Data collection methods include observation and questionnaires. The data analysis techniques used are classical assumption tests, multiple linear regression analysis, multiple correlation analysis, determination analysis, and t-tests. The results of this study indicate that financial knowledge and financial attitudes have a positive and significant effect on the financial management behavior of MSME players in West Denpasar, Denpasar City, but financial planning has a negative and significant effect on the financial management behavior of MSME players in West Denpasar, Denpasar City. For further research, it is recommended to add other variables so that the results can be generalized in a broader scope.